Pengukuran Kesehatan Mental Remaja dengan Self Reporting Quesionarre di SMPN 3 Ubud Gianyar - Anny Eka Pratiwi (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Adolescent mental health is an important aspect in human resource development because it affects learning ability, social relationships, and readiness to face adult life. Adolescence, especially at the junior high school level, is a transitional period that is prone to mental and emotional disorders due to biological, psychological, and social changes that occur simultaneously. This study aims to describe the mental health condition of adolescents using the Self Reporting Questionnaire (SRQ-20) instrument in students of SMPN 3 Ubud, Gianyar Regency. The study used a descriptive design with a cross sectional approach. The sampling technique was carried out in total sampling with a total of 117 students. The research instrument is in the form of an SRQ-20 questionnaire that has been proven to be valid and reliable. Data analysis was carried out descriptively to describe the distribution of symptoms and mental health categories of respondents. The results showed that most students were in the category of good mental health, although there were still a number of students with poor conditions. The most common symptoms are easy to feel tired and difficulty in making decisions. Based on the characteristics of respondents, students aged 13–15 years are more likely to experience poor mental health conditions than 11-13 years old, and the proportion of female students is higher than men in experiencing symptoms of mental emotional disorders. These findings affirm the importance of early detection of adolescent mental health in schools as the basis for promotive and preventive interventions, through optimizing the role of counseling guidance and creating a supportive school environment.